Microvascular Invasion in Hepatocellular Carcinoma: Some Puzzling Facets - Garzali, İbrahim Umar and Carr, Brian I and İnce, Volkan and Işık, Burak and Akatlı, Ayşe Nur and Yılmaz, Sezai (Turkish Journal of Gastroenterology, 2024)
Background/Aims: Hepatocellular carcinoma is the main type of primary liver cancer. Macroscopic vascular invasion is usually identified during imaging, whereas microvascular invasion is usually determined by histopathological evaluation. We aim to identify the association between microvascular invasion and other markers of tumor aggressiveness and to identify the role of microvascular invasion in the prognosis of patients who were treated by liver transplantation for hepatocellular carcinoma. Materials and Methods: This is a single-center retrospective analysis of prospectively collected data. Patients who received liver transplantation for hepatocellular carcinoma were included in the study. Data were collected regarding sociodemographic variables, criteria of selection for liver transplantation, pretransplant alpha-fetoprotein, presence or absence of microvascular invasion, presence or absence of recurrence, overall survival, and disease-free survival. Data were analyzed using Statistical Package for the Social Sciences. Results: Sociodemographic laboratory values and radiologic tumor characteristics were found to be similar in patients with or without microvascular invasion. Our study revealed that microvascular invasion is associated with increased recurrence, decreased diseasedfree survival, and decreased overall survival, only for patients with hepatocellular carcinoma beyond Milan criteria at the time of liver transplantation. Conclusion: For patients beyond Milan criteria, but not within Milan criteria, microvascular invasion plays a significant role in predicting recurrence and shorter survival after liver transplantation. Cite this article as: Garzali IU, Carr BI, İnce V, Işık B, Akatlı AN, Yılmaz S. Microvascular invasion in hepatocellular carcinoma: Some puzzling facets. Turk J Gastroenterol. 2024;35(2):143-149.